2017
DOI: 10.1016/j.foodhyd.2016.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Shear degradation of corn starches with different amylose contents

Abstract: a b s t r a c tThis work investigated the effect of shear on the starch degradation, with a particular focus on the changes in molecular and lamellar structures. Corn starches with different amylose/amylopectin ratios (waxy corn starch, or WCS: 1:99; normal corn starch, or NCS: 25:75; and Gelose 80 starch, or G80: 80:20) were used as model materials to be processed using a Haake twin-rotor mixer for different times. Molecular and lamellar structural analysis was performed using size-exclusion chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 34 publications
4
18
0
Order By: Relevance
“…However, this seems not to be an adequate explanation, as the decrease in available water would make the process more drastic, thus increasing the disruption of starch granules. The effect of shear stress in the extrusion process promoting starch gelatinization has been previously demonstrated by other authors …”
Section: Resultssupporting
confidence: 54%
“…However, this seems not to be an adequate explanation, as the decrease in available water would make the process more drastic, thus increasing the disruption of starch granules. The effect of shear stress in the extrusion process promoting starch gelatinization has been previously demonstrated by other authors …”
Section: Resultssupporting
confidence: 54%
“…Shear forces during extrusion disrupt granules and pull out amylose, as it happens during starch gelatinization in water. Moreover, amylopectin is more sensitive to these forces and can degrade during processing in the extruder [39,40,41], unraveling amylose and, instead of double helices, the single helices with plasticizer are formed. Such a big difference in crystallinity of TPS systems in dependence on processing methodology was also reported in other work [42], where XRD of TPS composite films were obtained from aqueous solution or by thermocompression at 150 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al () have also reported decrease in torques, though nonlinear upon increasing moisture levels. Liu et al () in their study on starches varying in amylose contents have concluded that rigid crystallites of amylopectin in starch granules is more susceptible to shear degradation compared with the flexible amorphous amylose. They recounted similarity of starch degradation mechanism to dry grinding mechanism of starch granules at a cryogenic temperature.…”
Section: Resultsmentioning
confidence: 99%